Development of an advanced nano-satellite VELOX-I attitude control system - Chia, Mun Weng. (2012)
The Velox-I, developed by Nanyang Technological University, is the first Singapore build nano-satellite and as with all satellites, it needs an Attitude Determination and Control System (ADCS). The ADCS is a subsystem that orientates the satellite so that the solar panels can face the sun and to point the camera to specific locations for image capturing.